Influence of silver nitrate (AgNO3) and cold pretreatment duration on the doubled haploid production of tomato using anther culture - Motallebi-Azar, Ali Reza (Progress in Nutrition, 2020)
The responses of tomato (cv. MSK8) anthers to different concentrations of silver nitrate and cold pretreatment duration were studied for producing doubled haploid (DH) plants via anther culture. Flower buds were collected from the plants grown in greenhouse conditions and isolated anthers were incubated on two cold pretreatment duration (CPD) (36 and 72 hrs) at 4°C under dark condition in four different silver nitrate (AgNO3) solutions with 0, 5, 10, 15 mg/l concentrations. Analysis of variance showed that interaction between AgNO3 and CPD was not significant for androgenic traits. However, CDP had significantly effects on measured traits. Achieved results reveled 36h CPD was more effective than 72h for studied traits. Callus and shoot induction, plantlet regeneration as well as green plants production were obtained from all the concentrations tested, but with significantly different rates. However, percentage of DH plant was not influenced by AgNO3 concentrations. The highest callus and shoot induction percentage and the number of plant regeneration were obtained from 5 mg/l AgNO3. The anthers pretreated by 10 mg/l AgNO3 produced more percentage of green plant production than that of the other concentrations. It seems that application of AgNO3 pretreatment had positive effects and can be proposed.